Pregnancy and heart disease: risk and predictors of obstetric complications - J., Cicily T.; Sams, Sherin; Alphonse, Soniya C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Although the disease is limited to only 0.5 to 1.0 percent of pregnant women, it remains an important cause of maternal morbidity and even mortality and has a significant effect on fetal outcome. Pregnancy and the peripartum period are associated with important cardiocirculatory changes that can lead to marked clinical deterioration in the woman with heart disease. Objectives of present study were to comprehend the impact of heart disease during pregnancy, to study the maternal and neonatal outcomes of pregnancies in women with heart disease, to identify predictors of pregnancy related complications in women with heart disease and to refine the risk stratification and to assess the individual risk of each pregnant woman with heart disease. Methods: It is a perspective study carried out at College Department of Obstetrics and Gynaecology, Govt. Medical, Kottayam from January 2012 to March 2014. Results: The outcomes of the pregnancies in 100 women who presented with heart disease and received their obstetrical care were evaluated. A maternal cardiac event, neonatal event, or both occurred in 37 completed pregnancies. A cardiac event complicated 8 completed pregnancies. It includes 2 maternal deaths, one on 9th postnatal day in women with hypertrophic obstructive cardiomyopathy and another in women with rheumatoid mitral stenosis who died of congestive cardiac failure. Most cardiac events (75%) occurred in the antepartum period and were either heart failure or cardiac arrhythmia. Conclusions: Strict prenatal care and early risk stratification during gestation are fundamental measures to improve the prognosis of pregnancy in women with heart disease.